Association of traumatic head injuries and maxillofacial fractures among patients treated at Hospital Universiti Sains Malaysia - Abosadegh, Maher Mahmoud Ahmed Ali (2018)
Background: The association of traumatic head injury (THI) with maxillofacial fractures (MFF) is major health concern worldwide. In spite of the close anatomical proximity of maxillofacial bones to the cranium, the association of THI with MFF is remained controversial as the patients with MFF are at high risk to sustain THI simultaneously. In such cases, recognition of the pattern of that association is an important information during initial assessment and treatment planning to reduce morbidity and mortality therefore improve the outcome of treatment. Objectives: This study assesses the association between THI and MFF among patients treated by Oral & Maxillofacial Surgery Unit and determine its prevalence. In addition, the other factors associated with THI in patients with MFF (age, sex, etiological causes, and types of MFF) and the Glasgow coma scale (GCS) score for those patients were also investigated. Materials and methods: A hospitalbased retrospective study at Hospital Universiti Sains Malaysia, Malaysia from June 12, 2013, to December 31, 2015 was conducted. A total of 473 patient records with MFF were reviewed in this study to evaluate the association of THI and MFF. The factors associated with THI were determined at both univariable and multivariable by using simple and multiple logistic regression analysis respectively to achieve that aim. The chi-square test was used for determining the association of GCS score. Results: Prevalence of THI among the patients with MFF was 69.98%. Cranial bonefractures (68.6%) being commonest of THI followed by intracranial injuries and concussion. Orbital wall fracture was the most frequent amongst patients with THI (61.0%), followed by fractures of maxillary sinus wall (36.9%), nasal bone (30.5%), and mandible bone (25.4%). A significant association exists between the GCS score and THI accompanying MFF with almost half of the patients (55.0%) had a mild head injury (GCS score 13-15). Motorcycle accident (MCA) was the most common cause of injury (75.8%), followed by motor vehicle accident (MVA) (10.9%) and fall (4.5%). The aetiology road traffic accident (RTA) and types of MFF (nasal bone, zygomatic complex, zygomatic arch, orbital wall, maxillary sinus wall and mandibular alveolar process) were statistically significantly associated with THI in patients with MFF [Adjusted odds ratio (AOR) = 4.65, 2.13, 2.37, 2.77, 3.38, 2.05, and 0.48 respectively]. Conclusion: A high prevalence of THI among patients with MFF (69.98%) considered as one of the highest percentagesworldwide. Although the majority of patients sustained mild head injuries of GCS score (13-15), the chance of THI still strongly suspected in those patients independent of GCS scores. Nasal bone, zygomatic complex, zygomatic arch, orbital wall, maxillary sinus wall and mandibular alveolar process fractures representing types of MFF which found statistically significant associated with THI in the patient sustained MFF while among the etiologies of injury only RTA was found statistically significant associated with THI.